IMPLEMENTASI PROGRAM KOTAKU MENYELESAIKAN PERSOALAN LINGKUNGAN KUMUH DI KRICAK YOGYAKARTA - Widiyanti, Imas; Baily, Ahmad; Mujadidi, Shibghotullah (Universitas Islam Negeri Raden Intan Lampung, 2021)
Kotaku is one of the programs launched and implemented by the local government to solve the problem of slum areas in Kricak, Tegalrejo, Yogyakarta. This study aims to determine the effectiveness of the program in overcoming environmental problems in the research location. This study uses a qualitative method with a naturalistic approach. Sources of data using primary and secondary data. Research data collection techniques through interviews, observation, and documentation. The validity of the data used triangulation. This study uses data analysis from the Miles and Huberman Model. Data analysis steps include data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Program Kotaku in the Kricak sub-district, Tegalrejo, Yogyakarta City has been running according to PU Number 40/SE/DC/2016. The implementation stage includes the socialization stage, the planning stage, the implementation stage and the sustainable stage. The impacts obtained from the arrangement of slum areas in the Kricak sub-district, Tegalrejo, Yogyakarta include changes in the physical environment to become more organized, clean and livable; raise public awareness to protect the environment together; and can improve the economy of the kricak community by utilizing public facilities that are well organized.